Clinical Profiles of Depressive and Stress-Related Phenotypes in Balinese Adolescents: A Retrospective Pilot Audit in a Secondary Care Setting - Ni Wayan Ika Widyaningsih (Scientia Psychiatrica, 2025)
Introduction: Adolescence represents a critical window of neurodevelopmental plasticity and psychosocial vulnerability. While tertiary centers in Indonesia frequently report high rates of psychosis, data regarding common mental disorders in rural secondary care settings remain scarce. This study aims to elucidate the clinical phenotypes and diagnostic divergence between early and late adolescence in a Balinese district hospital. Methods: This was a retrospective, observational pilot audit utilizing a total sampling strategy of all adolescent patients (aged 10–19 years) presenting to the Psychiatric Outpatient Clinic of Bangli Regional General Hospital throughout 2024. A total of 23 patients were eligible. Data regarding demographics, ICD-10 diagnoses, clinical severity (CGI-S), and psychosocial stressors were analyzed. Results: The clinical cohort (N=23) demonstrated a female predominance (n=14) and a skew toward late adolescence (n=17). A distinct diagnostic divergence was observed: Depressive episodes (F32) were the most frequent diagnosis (n=7), clustering predominantly in late adolescence (n=5), whereas adjustment disorders (F43.2) were exclusively identified in early adolescence (n=3). Anxiety disorders showed a notable male predominance (n=2 versus n=1 female). Clinical severity was higher in the late adolescent group, with a greater frequency of moderate-to-severe symptoms compared to the situational distress seen in younger teens. Conclusion: This pilot audit identifies a window of vulnerability for endogenous depressive pathology emerging in late adolescence (17–19 years), likely driven by academic transition pressures. Conversely, early adolescence is characterized by situational adaptability issues. The low utilization rate suggests significant barriers to care. Age-stratified interventions and school-based screenings are urgently recommended.